2013
DOI: 10.1037/a0030753
|View full text |Cite
|
Sign up to set email alerts
|

Converging identities: Dimensions of acculturation and personal identity status among immigrant college students.

Abstract: The present study was designed to ascertain the extent to which dimensions of acculturation would differ across personal identity statuses in a sample of 2,411, first and second generation immigrant college-attending emerging adults. Participants from 30 colleges and universities around the United States completed measures of personal identity processes as well as of heritage and American cultural practices, values, and identifications. Cluster-analytic procedures were used to classify participants into person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 89 publications
5
42
0
4
Order By: Relevance
“…Por tanto, la migración es entendida como un proceso de construcción social, que al ser dinámico, moviliza y que se relaciona estrechamente con la realidad subjetiva de la persona que migra (Schwartz et al, 2013;Veredas, 1999). En este sentido, el migrante construye una identidad en torno a su proceso de migrar, no solo desde las condiciones socio-económicas previas, sino también, desde una mirada de nueva territorialidad.…”
Section: Enmarcando El Problema: El Fenómeno Migratorio En Chileunclassified
See 1 more Smart Citation
“…Por tanto, la migración es entendida como un proceso de construcción social, que al ser dinámico, moviliza y que se relaciona estrechamente con la realidad subjetiva de la persona que migra (Schwartz et al, 2013;Veredas, 1999). En este sentido, el migrante construye una identidad en torno a su proceso de migrar, no solo desde las condiciones socio-económicas previas, sino también, desde una mirada de nueva territorialidad.…”
Section: Enmarcando El Problema: El Fenómeno Migratorio En Chileunclassified
“…De este modo, en el ámbito de los estudios migratorios no solo se considera relevante la construcción identitaria del sujeto como tal, sino también de los miembros de su familia, particularmente aquellos que nacen en el nuevo contexto cultural-territorial, como los hijos, quienes de alguna manera deben decidir "de dónde son" (Schwartz et al, 2013;Berry y Vedder, 2016). Al respecto, Portes (1997) releva las dificultades que enfrentan los hijos al crecer en una familia de migrantes, debido a que éstos buscan equilibrar la orientación de sus padres extranjeros con las demandas de "asimilación" de la sociedad y el territorio que lo recibe.…”
Section: Enmarcando El Problema: El Fenómeno Migratorio En Chileunclassified
“…The current findings also underscore the suggestion by Schwartz et al (2013) that exploration of an individual's personal identity and cultural identity may go hand in hand for members of different cultural and ethnic groups. This can be contrasted with the lack of findings regarding ethnic identity, and suggests that acculturation may be more salient than ethnic identity given the characteristics of the current sample.…”
Section: Study Ii: Marianismo Ethnic Identity Acculturation and Idementioning
confidence: 57%
“…Conversely, developing a strong ethnic identity has been associated previously with personal identity commitment. Finally, Schwartz et al (2013) found bicultural acculturation reflecting facility with and appreciation of both American and Hispanic culture was linked to personal identity achievement. Therefore, the following hypotheses were proposed for Study II.…”
Section: Study II Hypotheses: Marianismo Ethnic Identity and Accultmentioning
confidence: 99%
See 1 more Smart Citation